Indicators to Evaluate Base Running in Baseball, First Category from Mayabeque - H.G. Jose Luis; M.S. Jose Francisco; V. P. Mercedes (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
In the last seasons of the National Series there has been a loss of the possibilities in the base run by the first category Baseball players. In order to solve this problem, it is proposed as an objective: to develop indicators to evaluate the running of bases in the first category baseball team of Mayabeque. Theoretical methods Historical-logical, Inductive-deductive, Analysis-synthesis, the review of documents, observation of training units and games, the statistical results of the games in front of different teams, surveys, interviews and the measurement with the use of the HUMAN technique to detect the main deficiencies related to the race and other important factors of the base run was decisive to achieve the necessary effectiveness during the competitive exercise. The metrics demonstrate a solid framework and methodological foundation for evaluating base running performance. Validation was conducted using specific criteria, which confirmed their effectiveness in improving performance during training and competition.